2013
DOI: 10.1111/j.2047-6310.2012.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for genetic variants in BDNF that contribute to childhood obesity

Abstract: In silico analysis of the V46M variant did not support a clear disease-causing effect and no family data were available in order to determine whether the mutation segregates with obesity. However, we cannot rule out a possible pathogenic effect for this variant. In general, we tend to conclude that mutations in the coding region of BDNF are uncommon in obese patients and are therefore not likely to play an essential role in the pathogenesis of childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
1
3
0
1
Order By: Relevance
“…The associations reported herein were directionally consistent with results from GWAS: TMEM18 rs6548238 C‐allele , BDNF rs6265 G‐allele , rs10767664 A‐allele and NEGR1 rs2815752 A‐allele . Regarding BDNF , Zegers et al screened the coding region of the gene and did not find mutations associated with overweight or obesity in children and adolescents . On the other hand, Gardner et al revealed BDNF promoter methylation levels associated with satiety responsiveness in female children .…”
Section: Discussionsupporting
confidence: 85%
“…The associations reported herein were directionally consistent with results from GWAS: TMEM18 rs6548238 C‐allele , BDNF rs6265 G‐allele , rs10767664 A‐allele and NEGR1 rs2815752 A‐allele . Regarding BDNF , Zegers et al screened the coding region of the gene and did not find mutations associated with overweight or obesity in children and adolescents . On the other hand, Gardner et al revealed BDNF promoter methylation levels associated with satiety responsiveness in female children .…”
Section: Discussionsupporting
confidence: 85%
“…They have found the p.(Thr2Ile) variant in three subjects with obesity, but it was also present with comparable frequency in their control group. 30 This variant was found in 1000 Genomes Project, ExAC database, and ABraOM. All these results suggest that the p.Thr2Ile is a rare, but a non-disease causing variant.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our SNS probands, postnatal abnormalities were not reported. Additionally, association of the p.2Ile allele with weight regulation has not yet been detected [ 42 , 43 ]. The frequency of the p.2Ile allele in our SNS study group (0.54%) is comparable with other studies (0.55%; [ 42 ]; 0.53%; [ 43 ]), hence a relevance in weight regulation and SNS is unlikely.…”
Section: Discussionmentioning
confidence: 99%